Resonance interaction between two entangled gravitational polarizable objects - Yongshun Hu; Jiawei Hu; Hongwei Yu; Puxun Wu (European Physical Journal C: Particles and Fields, 2020)
Abstract We investigate the resonance quadrupole-quadrupole interaction between two entangled gravitationally polarizable objects induced by a bath of fluctuating quantum gravitational fields in vacuum in the framework of linearized quantum gravity. Our result shows that, the interaction energy behaves as $$r^{-5}$$ r-5 in the near regime, and oscillates with a decreasing amplitude proportional to $$r^{-1}$$ r-1 in the far regime, where r is the distance between the two objects. Compared to the case when the two objects are in their ground states, the quantum gravitational interaction is significantly enhanced when the objects are in an entangled state. Remarkably, in the far regime, the resonance quantum gravitational interaction can give the dominating quantum correction to the Newtonian potential, since the extremum is much greater than the monopole-monopole quantum gravitational interaction.